Treatment of Idiopathic Normal Pressure Hydrocephalus with a Novel Programmable Valve: Prospective Evaluation of Costs, Efficacy, and Safety - Reis, Rodolfo Casimiro; Yamashita, Renata Harumi Gobbato; Solla, Davi Jorge Fontoura; Ramin, Laís Fajardo; Teixeira, Manoel Jacobsen; Pinto, Fernando Campos Gomes (Asian Journal of Neurosurgery, 2023)
Objective Programmable valves provide an equal or superior neurological outcome when compared with fixed pressure ones, with fewer complications, in treating idiopathic normal pressure hydrocephalus (iNPH) patients. Long-term costs of these treatments have not been properly compared in literature. We sought to compare costs, efficacy, and safety of 1-year treatment of iNPH patients with programmable valve Sphera Pro and a fixed pressure valve.Materials and Methods A prospective cohort of iNPH patients treated with programmable valve was compared with a historical cohort of iNPH patients treated with fixed pressure valve. Our primary outcome was mean direct cost of treating iNPH up to 1 year. Efficacy in treating iNPH and safety were assessed as secondary outcomes.Statistical Analysis Proportions were compared using chi-square or Fisher's exact tests. Normally distributed variables were compared using the Student's t-test or the Mann–Whitney's U test. Differences in the evolution of the variables over time were assessed using generalized estimating equations. All tests were two-sided, with an α of 0.05.Results A total of 19 patients were analyzed in each group (mean age 75 years, the majority male). Comorbidities and clinical presentation were similar between groups. Both fixed pressure and programmable valve patients had neurological improvement over time (p < 0.001), but no difference was seen between groups (p = 0.104). The fixed pressure valve group had more complications than the programmable valve group (52.6% vs. 10.5%, respectively, p = 0.013). Annual treatment cost per patient was US$ 3,820 ± 2,231 in the fixed pressure valve group and US$ 3,108 ± 553 in the programmable valve group. Mean difference was US$712 (95% confidence interval, 393–1,805) in favor of the programmable valve group.Conclusion The Sphera Pro valve with gravitational unit had 1 year treatment cost not higher than that of fixed pressure valve, and resulted in similar efficacy and fewer complications.
Keywords: cost analysis; efficacy; normal pressure hydrocephalus; safety; ventriculoperitoneal shunt